2018
DOI: 10.1111/bcpt.13082
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Decreases Hepatic Inflammation and Injury in Advanced Lean Non‐Alcoholic Steatohepatitis

Abstract: Although commonly associated with obesity, non-alcoholic fatty liver disease (NAFLD) is also present in the lean population representing a unique disease phenotype. Affecting 25% of the world's population, NAFLD is associated with increased mortality especially when progressed to non-alcoholic steatohepatitis (NASH). However, no approved pharmacological treatments exist. Current research focuses mainly on NASH associated with obesity, leaving the effectiveness of promising treatments in lean NASH virtually unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…We note that NAFLD is also a frequent comorbidity in patients with nonobese patients with T2DM [12]. Additionally, a preclinical trial of GLP-1RA demonstrated decreased liver inflammation and injury in lean patients with nonalcoholic steatohepatitis [41]. Our cohort of normal BMI T2DM patients can be diagnosed as hepatic steatosis because of high LFC, whereas those treated with exenatide exhibited the largest decreases in this parameter after the 24-week intervention.…”
mentioning
confidence: 61%
“…We note that NAFLD is also a frequent comorbidity in patients with nonobese patients with T2DM [12]. Additionally, a preclinical trial of GLP-1RA demonstrated decreased liver inflammation and injury in lean patients with nonalcoholic steatohepatitis [41]. Our cohort of normal BMI T2DM patients can be diagnosed as hepatic steatosis because of high LFC, whereas those treated with exenatide exhibited the largest decreases in this parameter after the 24-week intervention.…”
mentioning
confidence: 61%
“…GLP is a peptide derived from the L cells of the lower gastrointestinal tract (the small intestine and proximal colon) and known to enhance insulin secretion from pancreatic β cells and inhibit glucagon release from pancreatic α cells (Campbell and Drucker 2013;Ratziu et al 2015). Whereas the GLP1R agonist exenatide enhanced hepatic steatosis (Tanaka et al 2014), hepatic oxidative stress, and hepatic inflammation (Shao et al 2018) and improved adipose tissue lipolysis in different in vivo models, the application of dulaglutide, lixisenatide, liraglutide, and, recently, semaglutide also shows promising results in terms of improvements in hepatic fat, damage, inflammation, and fibrosis (Armstrong et al 2016;Cusi et al 2018;Ipsen et al 2018;Koutsovasilis et al 2018;Petit et al 2017;Rakipovski et al 2018).…”
Section: Targeting Insulin/glucose Metabolismmentioning
confidence: 99%
“…1 However, there is an outstanding gap in literature regarding the efficacy and safety of pharmacologic agents, in general, and of novel antidiabetics, in specific, for the management of lean NAFLD, except for some sparse experimental data. 8 Thus, based on the aforementioned epidemiologic data, there is an urgent need for well-designed prospective studies enrolling lean NAFLD subjects to investigate the efficacy and safety of the promising novel antidiabetics.…”
Section: Dear Editormentioning
confidence: 99%